Respuesta :
ANSWER
The value of d that makes the equation true is
[tex]d = - 2[/tex]
EXPLANATION
The given equation is
[tex]10(d + 3) - ( - 9d - 4) = d - 5 + 3[/tex]
We expand brackets to obtain,
[tex]10d + 30 + 9d + 4= d - 5 + 3[/tex]
We group like terms to obtain,
[tex]10d +9d - d = - 30 - 5 + 3 - 4[/tex]
This simplifies to
[tex]18d = - 36[/tex]
We divide both sides by 18 to get,
[tex]d = - 2[/tex]
The value of d that makes the equation true is
[tex]d = - 2[/tex]
EXPLANATION
The given equation is
[tex]10(d + 3) - ( - 9d - 4) = d - 5 + 3[/tex]
We expand brackets to obtain,
[tex]10d + 30 + 9d + 4= d - 5 + 3[/tex]
We group like terms to obtain,
[tex]10d +9d - d = - 30 - 5 + 3 - 4[/tex]
This simplifies to
[tex]18d = - 36[/tex]
We divide both sides by 18 to get,
[tex]d = - 2[/tex]
Answer:
d=-2
Step-by-step explanation:
We have
[tex]10(d+3)-(-9d-4)=d-5+3[/tex]
now we remove parenthesis and use distribution property
[tex]10d+30+9d+4=d-5+3[/tex]
now we combine like terms
[tex]10d+9d+30+4=d-2[/tex]
[tex]19d+34=d-2[/tex]
[tex]19d-d+34=-2[/tex] (subtract d from both side )
[tex]18d=-2-34[/tex] ( subtract 34 from both side )
[tex]18d=-36[/tex]
[tex]d=\frac{-36}{18}[/tex] ( divide both side by 18)
[tex]d=-2[/tex]